Similar migration for medial congruent and cruciate-retaining tibial components in an anatomic TKA system: a randomized controlled trial of 60 patients followed with RSA for 2 years - Christensson, Albin; Tveit, Magnus; Kesteris, Uldis; Flivik, Gunnar (Acta Orthopaedica, 2022)
Background and purpose — There is an ongoing debate regarding the appropriate level of constraint in primary TKA. To provide increased stability and better kinematics, more resembling a natural knee, a medial congruent (MC) tibial insert has been introduced. To investigate potential impact on implant migration, we evaluated the cemented Persona TKA, randomizing between MC and cruciate-retaining (CR) tibial designs. Patients and methods — 60 patients with primary osteoarthritis were randomized to either the CR or MC tibial component. Radiostereometric analysis (RSA) examinations, evaluating translational and rotational migration as well as maximal total point motion (MTPM), were performed on the first postoperative day, at 3 months, and 1 and 2 years after surgery. Preoperative, and 1- and 2-year patientreported outcome measures (PROMs) data (KOOS and FJS) were collected. Results — The mean tibial MTPM at 3 months were 0.48 mm (95% CI 0.37–0.58) and 0.56 mm (0.45–0.67) for the CR and MC respectively. 2 years postoperatively the respective values were 0.62 mm (0.50–0.73) and 0.73 mm (0.49–0.96). There was no statistically significant difference in migration between groups, for either the femoral or the tibial component, regarding x-, y-, and z-translations or rotations. Both CR and MC groups improved as expected in PROM scores pre- to postoperatively, but without a statistically significant difference between groups. There were no revisions or other serious adverse events related to surgery. Interpretation — The results are promising, indicating good fixation for both designs, and this is in line with other well-performing TKAs on the market. The increased medial congruity of the MC inlay does not seem to affect the migration or the PROMs up to 2 years.